The effect of using the Discovery learning Method on the Logic and Mathematical Thinking of sixs Graders. (A Semi-experimental study in Latakia ) - غصون سماح; نصور رغداء (Latakia University Journal - Arts and Humanities Sciences Series, 2022)
The research learning method in logical mathematical thinking and revealing the differences between males and females among a sample of six grade students consisting of (60) male and female students. Using the experimental method, Where the study tools were designed, and their validity and reliability were confirmed, then the sample was choosen, it was divided into two groups; the first experimental group consisting of (30) male and female students and the second control group consisting of (30) male and female students, their equivalence was confirmed, the experimental group studied according to the discovery method, and the control group according to the usual method, after extracting the results, analyzing them statistically, the following results appeared at the level of significance (0.05) there are statistically significant differences between the mean scores of the students of the experimental and control groups in the slave application of the mathematical logical thinking scale in favor of the experimental group.